Documenting queer(ed) punk histories: Instagram, archives and ephemerality. (1st June 2018) - Rosenberg, Shoshana; Sharp, Megan
Queer(ed) bodies in punk subculture problematize deeply embedded heterosexual, cismale occupation of space and time. Traditional modes of media and documentation aid in establishing normative perspectives of who participates in punk, and how. Rather than reproducing dominant media expectations, queer people express and explore their self(s) through mediating fleeting-yet-concrete utopias that often leave only ephemeral evidence, but are picked up from the margins of scenes and media by others who know where to find them. This article examines tattooing and its intersection with Instagram digitization as forms of memorialising identity, not necessarily through the artwork of the tattoo, but rather through the praxis and application of its subject. Through a reflexive analysis of interviews with queer people who have been involved with punk, as well as the authors' autoethnographic reflections on their own experiences as queers in punk scenes and on Instagram, this article explores tattoo practice as a means of creating affective atmospheres and embodying queer futurity. We find that tattoos act as silos for bodily and digital memory, and that their utility for queer punx generates new forms of meaning, mediation and production.